2013
DOI: 10.1515/ntrev-2012-0051
|View full text |Cite
|
Sign up to set email alerts
|

Why is the nanoscale special (or not)? Fundamental properties and how it relates to the design of nano-enabled drug delivery systems

Abstract: Why is the nanoscale special (or not) ?Fundamental properties and how it relates to the design of nano-enabled drug delivery systems Abstract: Nanoscience studies describe natural phenomena at the submicron scale. Below a critical nanoscale limit, the physical, chemical, and biological properties of materials show a marked departure in their behavior compared to the bulk. At the nanoscale, energy conversion is dominated by phonons, whereas at larger scales, electrons determine the process. The surface-to-volum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 197 publications
0
5
0
Order By: Relevance
“…SnO 2 nanoparticles (NP) are particularly interesting due to they have better performance on solar cells compared to their bulk counterparts [2]. High pressure (HP) experiments are becoming more and more extending over nanomaterials because of the new and potentially interesting properties discovered [3][4][5]. For instance, it has been shown that oxides nanoparticles (NP) could present different transition pressures [6][7][8][9] and different phase transformation sequences [6], presenting on many studies also different compressibilities compared to their bulk counterparts [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…SnO 2 nanoparticles (NP) are particularly interesting due to they have better performance on solar cells compared to their bulk counterparts [2]. High pressure (HP) experiments are becoming more and more extending over nanomaterials because of the new and potentially interesting properties discovered [3][4][5]. For instance, it has been shown that oxides nanoparticles (NP) could present different transition pressures [6][7][8][9] and different phase transformation sequences [6], presenting on many studies also different compressibilities compared to their bulk counterparts [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…This periodic behavior is ensured by the reversal of the net surface charge after complete adsorption of each layer. 59,60 For these systems, the time required for magnetic moment reversal along the easy magnetization axis follows an Arrheniuslike behavior governed by expression (1). 55 A representative cross-sectional high resolution transmission electron microscopy (HRTEM) micrograph of nanofilms comprised by polyaniline and maghemite (PANI/J-n-MAG) is shown in Figure 5 (a).…”
Section: Nanofilm Assembly Monitoring and Propertiesmentioning
confidence: 99%
“…1 Part of these advances have been achieved thanks to colloidal chemistry methods that provide much simpler and affordable routes for the preparation of nanomaterials in comparison to more sophisticated methods such as nanolithography, molecular beam epitaxy, and laser patterning. 1 Part of these advances have been achieved thanks to colloidal chemistry methods that provide much simpler and affordable routes for the preparation of nanomaterials in comparison to more sophisticated methods such as nanolithography, molecular beam epitaxy, and laser patterning.…”
Section: Introductionmentioning
confidence: 99%
“…This special interest in NMs arises from the improvement of some nanoscale properties with respect to the properties of analogous bulk materials [2]. Such behaviour is due to the appearance of the "quantum size effect" from the electronic wavefunction, to the limited physical dimensions of the nanoparticle (NP), being this effect just limited to the nanoscale [3,4]. Owing to this confinement at the nanoscale, the phonons on which thermal, optical, and conductive properties depend, will impart distinctive characteristics to the NMs compared to the unconfined and macroscopic counterparts, with a like-photons behaviour.…”
Section: Introductionmentioning
confidence: 99%